2018
DOI: 10.1111/maps.13143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of target properties and impact velocity on ejection dynamics and ejecta deposition

Abstract: Impact craters are formed by the displacement and ejection of target material. Ejection angles and speeds during the excavation process depend on specific target properties. In order to quantify the influence of the constitutive properties of the target and impact velocity on ejection trajectories, we present the results of a systematic numerical parameter study. We have carried out a suite of numerical simulations of impact scenarios with different coefficients of friction (0.0–1.0), porosities (0–42%), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 61 publications
(203 reference statements)
13
62
0
Order By: Relevance
“…, ) comparable to funneled craters in highly porous snow (Luther et al. , Forthcoming). Saturation of pore space with water at 50 and 90%, respectively, set off the effects of porosity, with crater size increasing with progressive saturation of target pore space (Dufresne et al.…”
Section: Crater Morphologies and Cratering Efficienciesmentioning
confidence: 82%
See 1 more Smart Citation
“…, ) comparable to funneled craters in highly porous snow (Luther et al. , Forthcoming). Saturation of pore space with water at 50 and 90%, respectively, set off the effects of porosity, with crater size increasing with progressive saturation of target pore space (Dufresne et al.…”
Section: Crater Morphologies and Cratering Efficienciesmentioning
confidence: 82%
“…Complementary numerical modeling of the ejection process shows that the ejection angle and velocity depend on porosity, friction, and cohesion (Luther et al. ). Increasing the coefficient of friction and the porosity of the target material leads to a decrease of ejection velocities and the formation of smaller craters.…”
Section: Ejecta Dynamicsmentioning
confidence: 99%
“…For example, for ejecta a with a launch velocity of V , we calculate its normal velocity ( V r ) and tangent velocity ( V t ), from which the launch angle is estimated to be θ = atan ( V r / V t ; see Figure a). This method has been used previously in several modeling studies on the ejecta distribution (e.g., Luther et al, ; Wünnemann et al, ). Although the ejecta behave more as a continuous flow with partly fluidized melt, they move along parabolic trajectories and land on the lunar surface with approximately the same velocity as launched.…”
Section: Ejecta and Crustal Thickness Calculation Of Giant Impact Eventmentioning
confidence: 99%
“…During the excavation stage of crater formation, a large amount of material is ejected ballistically out of the crater as ejecta (Oberbeck, 1975;Housen et al, 1983). Previous laboratory (Housen and Holsapple, 2011) and numerical studies (Jutzi and Michel, 2014;Luther et al, 2018;Raducan et al, 2019) of impact events into homogeneous targets have shown that the speed and mass of ejecta depends sensitively on target material properties, such as cohesive strength, porosity and the coefficient of internal friction. However, most bodies in the Solar System are not homogeneous, as shown by past missions to asteroids, such as the NEAR-Shoemaker (Veverka et al, 2001), the OSIRIS-REx (Lauretta et al, 2019;Walsh et al, 2012) or the Hayabusa missions (Yano et al, 2006;Watanabe et al, 2019), as well as Earth-based thermal infrared observations (Delbo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%